Supervisi Akademik Sebagai Upaya Untuk Meningkatkan Kinerja Guru Pendidikan Agama Islam Dan Budi Pekerti (PAIBP) Sekolah Dasar Di Kota Binjai - Ikhsanti Hannum (Jurnal Analisa Pemikiran Insan Cendikia (Jurnal APIC), 2021)
This paper describes enhancement in teacher performance in implementing the learning process, after academic supervision is carried out. Transformation in the form of attendance, fulfillment of work tools, time discipline, use of media, and teaching skills are indicators of this. The method used for research is qualitative with quantitative data collection and analysis techniques, and Classroom Action Research approach. The number of teachers used as a sample was 20 people, and the results obtained showed that after the research was carried out in cycle I and cycle II, a total of 85% sampled for 10 aspects of the assessment increased their performance. This data shows the achievement of the successful implementation of supervisory academic supervision of PAIBP teachers.